1980
DOI: 10.1116/1.570540
|View full text |Cite
|
Sign up to set email alerts
|

Erratum: New and unified model for Schottky barrier and III–V insulator interface states formation [J. Vac. Sci. Technol. 16, 1422 (1979)]

Abstract: Articles you may be interested inErratum: Use of Raman spectroscopy to characterize strain III-V epilayers: Application to InAs on GaAs(001) grown by molecularbeam epitaxy [J.Addendum: Cryopump measurements relating to safety, pumping speed, and radiation outgassing [J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
128
0
13

Year Published

2000
2000
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(146 citation statements)
references
References 0 publications
5
128
0
13
Order By: Relevance
“…Most of the previous models for Fermi level pinning assume presence of interface states whose charging screens the metal electronegativity. The origin of the interface states is ascribed to stoichiometry related defect states (Unified Defect model [40]), to metal induced gap states (MIGS model [41,42]) or to disorder induced gap states (DIGS model [43]). …”
Section: Fermi Level Pinning At Metal-semiconductor Interfacesmentioning
confidence: 99%
“…Most of the previous models for Fermi level pinning assume presence of interface states whose charging screens the metal electronegativity. The origin of the interface states is ascribed to stoichiometry related defect states (Unified Defect model [40]), to metal induced gap states (MIGS model [41,42]) or to disorder induced gap states (DIGS model [43]). …”
Section: Fermi Level Pinning At Metal-semiconductor Interfacesmentioning
confidence: 99%
“…The As Ga defects form double donor levels 0.52 eV and 0.75 eV above the valence band. 41 The concentration of these defects can be as high as 10 20 cm Ϫ3 in LT GaAs films grown at 260-270°C. Tunnelling spectroscopy measurements for such samples have shown that these levels broaden to form a midgap deep donor band centered Ӎ0.5 eV above the valence band.…”
Section: A Spectroscopic Signatures Of Compensation In Ga 1àx Mn X Asmentioning
confidence: 99%
“…As a possible origin of the FLP at the metal=semiconductor interface, metal-induced gap states (MIGS), 24) bond polarization, 25) disorder-induced gap states (DIGS) 26) or defects 27) have been long discussed. In this work, we reexamine the FLP on n-Ge on the basis of the MIGS model, that is, the tail of the electron wave function in a metal is intrinsically penetrated into the semiconductor.…”
mentioning
confidence: 99%